2018
DOI: 10.31373/ejtcm/95222
|View full text |Cite
|
Sign up to set email alerts
|

Does the age of patients with hereditary hemochromatosis at the moment of their first diagnosis have an additional effect on the standard echocardiographic parameters?

Abstract: Background: Hereditary haemochromatosis (HH) is an inherited disease in which gene mutation leads to excessive iron absorption and accumulation in different organs, including the heart, which causes damage. Whether the age of patients with HH at the moment of their first diagnosis has an additional effect on the standard echocardiographic parameters was the aim of the study. Material and methods: We prospectively enrolled 20 HH patients, and 20 healthy age-and sex-matched volunteers. Analysis of standard echoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the group of patients with the newly diagnosed disease, showing no clinical symptoms yet, seems to be very interesting from a clinical point of view. In one of our previous studies [ 78 ], based on such patients, we found many differences in parameters referring to the diastolic function and the thickness of the left ventricle compared to healthy people. It is worth noting that differences were more expressed and included more parameters (Em, E/Em, left atrium area index, relative wall thickness) in older (≥50 years old) compared to age-matched healthy persons than in younger patients with HH.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the group of patients with the newly diagnosed disease, showing no clinical symptoms yet, seems to be very interesting from a clinical point of view. In one of our previous studies [ 78 ], based on such patients, we found many differences in parameters referring to the diastolic function and the thickness of the left ventricle compared to healthy people. It is worth noting that differences were more expressed and included more parameters (Em, E/Em, left atrium area index, relative wall thickness) in older (≥50 years old) compared to age-matched healthy persons than in younger patients with HH.…”
Section: Resultsmentioning
confidence: 95%
“…Shizukuda et al, additionally pay attention to the increased contractility of the left atrium as an early expression of diastolic dysfunction [ 77 ]. In many publications, changes reported in diastolic function in patients with HH were focused on patients with a long-lasting and long-treated HH [ 17 , 78 , 79 ]. We observed these changes in our patients with more than ten years HH history either.…”
Section: Resultsmentioning
confidence: 99%
“…The latter had worse LV wall thickness, RWT, LVM index, and Em indices, probably due to the disease's length and the patient's age ( Table 4 , Figure 3 ). Hypertension and glucose disturbances, which occur earlier in patients with HH than in the overall population, could have an additional impact on the left ventricular diastolic function ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload may accelerate the aging of the cardiovascular system, including the heart, through oxidative stress, which results in appropriate changes in diastolic and systolic parameters. These changes can be detected by standard echocardiography (increase in the LV width and LVM index, LA enlargement, or changes in mitral flow parameters) or by STE (decrease in rotation, twist, and torsion values of the LV) ( 10 , 15 17 ).…”
Section: Discussionmentioning
confidence: 99%